2008
DOI: 10.1111/j.1744-7909.2008.00752.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Elevated CO2 and Drought on Soil Microbial Communities Associated with Andropogon gerardii

Abstract: Our understanding of the effects of elevated atmospheric CO 2 , singly and in combination with other environmental changes, on plant-soil interactions is incomplete. Elevated CO 2 effects on C 4 plants, though smaller than on C 3 species, are mediated mostly via decreased stomatal conductance and thus water loss. Therefore, we characterized the interactive effect of elevated CO 2 and drought on soil microbial communities associated with a dominant C 4 prairie grass, Andropogon gerardii Vitman. Elevated CO 2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 66 publications
2
14
1
Order By: Relevance
“…It can, therefore, be expected that prolonged summer droughts will decrease priming. However, as plants have better water use efficiency at elevated CO 2 (Field et al, 1995;Ainsworth and Rogers, 2007), drought impacts on microbial activity are in some cases less severe when combined with elevated CO 2 (Kassem et al, 2008). The combined effect of elevated CO 2 and drought on the magnitude of priming is to our knowledge not known.…”
Section: Introductionmentioning
confidence: 89%
“…It can, therefore, be expected that prolonged summer droughts will decrease priming. However, as plants have better water use efficiency at elevated CO 2 (Field et al, 1995;Ainsworth and Rogers, 2007), drought impacts on microbial activity are in some cases less severe when combined with elevated CO 2 (Kassem et al, 2008). The combined effect of elevated CO 2 and drought on the magnitude of priming is to our knowledge not known.…”
Section: Introductionmentioning
confidence: 89%
“…For example, BassiriRad [21] reviewed effects of elevated CO 2 on root nutrient uptake kinetics, and Taub and Wang [93] reviewed studies relating to the mechanism of CO 2 effects on shoot %N. However, in response to elevated CO 2 , soil microbial biomass and activity have been observed to decrease, increase, or remain unchanged (e.g., [94][95][96]). However, in response to elevated CO 2 , soil microbial biomass and activity have been observed to decrease, increase, or remain unchanged (e.g., [94][95][96]).…”
Section: Heat Stress and Root---soil Interactionsmentioning
confidence: 99%
“…CO 2 concentrations are generally much higher in the pore spaces of soil (2000–3800 μmol mol −1 ) than in the atmosphere, so elevated CO 2 usually influences the richness, composition, and structure of the communities indirectly, such as by increasing plant carbon (C) inputs to the soil and altering soil properties 7 . Phospholipid fatty acid (PLFA) analysis and denaturing gradient gel electrophoresis indicated that CO 2 enrichment had no detectable effects on the composition and structure of the community 812 , but usually stimulated soil respiration 11, 13 . Analyses of functional genes indicated that elevated CO 2 decreased the expression of genes involved in the C and N cycles 14, 15 , but Liu et al .…”
Section: Introductionmentioning
confidence: 99%